2014
DOI: 10.5430/jnep.v4n5p23
|View full text |Cite
|
Sign up to set email alerts
|

Fostering enthusiasm for research: Insights of undergraduate nursing students

Abstract: Engaging undergraduate nursing students in research is essential to promoting evidence-informed nursing, but can prove challenging. The purpose of this article is to highlight key experiences of four undergraduate nursing students who are enthusiastic about research with the potential to inform the education and training of undergraduate nursing students in research. Analysis of our own experiences emphasized that enthusiasm for research is promoted by the following factors: love of learning, opportunities for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In an integrative review about nursing students' attitudes toward research, Ross and Burrell (2019) concluded that factors such as taking a research course, having an interest in a particular area of nursing research, application of research knowledge, or having prior research experience were associated with an improvement in undergraduate students' attitudes toward nursing research (Ross & Burrell, 2019). Moreover, Warkentin et al (2014) analyzed the experiences of four undergraduate nursing students who were enthusiastic about research and concluded that students found that collaboration and support were necessary factors to generate and maintain enthusiasm for research. Collaboration implies working alongside researchers, collaborators, and other students in the research processes.…”
Section: Objectives Activities Carried Out In Collaboration With and Under The Guidance Of A Supervisormentioning
confidence: 99%
See 1 more Smart Citation
“…In an integrative review about nursing students' attitudes toward research, Ross and Burrell (2019) concluded that factors such as taking a research course, having an interest in a particular area of nursing research, application of research knowledge, or having prior research experience were associated with an improvement in undergraduate students' attitudes toward nursing research (Ross & Burrell, 2019). Moreover, Warkentin et al (2014) analyzed the experiences of four undergraduate nursing students who were enthusiastic about research and concluded that students found that collaboration and support were necessary factors to generate and maintain enthusiasm for research. Collaboration implies working alongside researchers, collaborators, and other students in the research processes.…”
Section: Objectives Activities Carried Out In Collaboration With and Under The Guidance Of A Supervisormentioning
confidence: 99%
“…Concerning support, students identified, for example, training sessions in research programs. Collaboration and support opportunities served to increase students' confidence and practical skills, resulting in them realizing their potential as researchers and, subsequently, their ability to pursue their studies (Warkentin et al, 2014).…”
Section: Objectives Activities Carried Out In Collaboration With and Under The Guidance Of A Supervisormentioning
confidence: 99%
“…Therefore, statements such as, 'Guiding someone through his/her research in case of having relevant experience' and 'Being happy about providing support for research' are included in the scale. Overcoming difficulties encountered regarding research is suggested to encourage enthusiasm towards research (Warkentin et al, 2014). This is reflected in the scale as the 'Ability to stay calm in the event of a crisis' and 'Ability to find alternatives in the event of a crisis'.…”
Section: Sub-dimensions Of the Srcsmentioning
confidence: 99%
“…Underlying these research content issues is the lack of exposure of students to PhD-prepared nurse scientists conducting rigorous and practice-relevant research (Hickey, 2018;Warkentin, Popik, Usick, & Farley, 2014). In research intensive universities where students are perhaps most likely to gain exposure to rigorous nursing science, faculty with active research funding often are released from teaching obligations to focus on conducting their studies.…”
Section: Lack Of Exposure Of Nursing Students To Researchmentioning
confidence: 99%